2011
DOI: 10.1177/1086296x10397872
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Diversity

Abstract: This study examined the relative contribution of reading comprehension strategies and interactive vocabulary in Improving Comprehension Online (ICON), a universally designed web-based scaffolded text environment designed to improve fifthgrade monolingual English and bilingual students' reading achievement. Seventy-five monolingual English and 31 bilingual students from six classrooms were assigned to one of three ICON conditions: reading comprehension strategies, vocabulary, or a combined version of comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Other studies have indicated that certain kinds of texts and tasks may enhance cognitive capabilities for readers who struggle in traditional print-reading environments. This research has included, for example, work exploring the affordances of computer-assisted instruction for students with attention deficit disorders (Raggi & Chronis, 2006), learning disabilities (Hall, Hughes, & Filbert, 2000), or intellectual disabilities (Snyder & Huber, 2019), as well as studies applying principles of Universal Design for Learning to support diverse readers with flexible learning environments and accessible content (Coyne, Pisha, Dalton, Zeph, & Smith, 2012;Dalton, Proctor, Uccelli, Mo, & Snow, 2011). Still others have focused on the collaborative use of graphic representational tools (Kiili, Coiro, & Hämäläinen, 2016) or the metacognitive scaffolding of online information search practices (Zhou & Lam, 2019) to support the cognitive processing abilities of diverse learners in digital spaces.…”
Section: Cognitive Capabilitiesmentioning
confidence: 99%
“…Other studies have indicated that certain kinds of texts and tasks may enhance cognitive capabilities for readers who struggle in traditional print-reading environments. This research has included, for example, work exploring the affordances of computer-assisted instruction for students with attention deficit disorders (Raggi & Chronis, 2006), learning disabilities (Hall, Hughes, & Filbert, 2000), or intellectual disabilities (Snyder & Huber, 2019), as well as studies applying principles of Universal Design for Learning to support diverse readers with flexible learning environments and accessible content (Coyne, Pisha, Dalton, Zeph, & Smith, 2012;Dalton, Proctor, Uccelli, Mo, & Snow, 2011). Still others have focused on the collaborative use of graphic representational tools (Kiili, Coiro, & Hämäläinen, 2016) or the metacognitive scaffolding of online information search practices (Zhou & Lam, 2019) to support the cognitive processing abilities of diverse learners in digital spaces.…”
Section: Cognitive Capabilitiesmentioning
confidence: 99%
“…Topic-specific word banks or word walls, combined with an online Work Log and a follow-up quiz, are some of the activities that would serve this purpose. The Online Work Log (Dalton, Proctor, Uccelli, Mo & Snow, 2011) has three components: 1) Connect It! (where the reader/writer is asked to make personal connection to a target concept/ term, as in this example, " Generation [target concept/word]: I am the fourth generation in my family that's still living" (p.82); 2) Web It!…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Many of these technology-based interventions are conceived as digital strategy coaches that attempt to replicate the interactions that students might expect in a collaborative classroom situation (Dalton & Strangman, 2006). Others are supported text reading environments, in which texts are altered or supplemented in an effort to lower or eliminate barriers to access and increase readers' ability to extract meaning (Anderson-Inman & Horney, 1997Dalton, Proctor, Uccelli, Mo, & Snow, 2011;Dalton & Proctor, 2008;Dalton & Strangman, 2006).…”
Section: Technology and Reading Comprehensionmentioning
confidence: 99%
“…Take, for example, the Improving Comprehension Online (ICON) system (Dalton et al, 2011). The ICON system is "a universally designed Web-based scaffolded text environment designed to improve fifthgrade monolingual English and bilingual students' reading achievement" (Dalton et al, 2011, p. 68).…”
Section: Technology and Reading Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation